2006
DOI: 10.1016/j.cell.2005.12.034
|View full text |Cite
|
Sign up to set email alerts
|

DEMETER DNA Glycosylase Establishes MEDEA Polycomb Gene Self-Imprinting by Allele-Specific Demethylation

Abstract: MEDEA (MEA) is an Arabidopsis Polycomb group gene that is imprinted in the endosperm. The maternal allele is expressed and the paternal allele is silent. MEA is controlled by DEMETER (DME), a DNA glycosylase required to activate MEA expression, and METHYLTRANSFERASE I (MET1), which maintains CG methylation at the MEA locus. Here we show that DME is responsible for endosperm maternal-allele-specific hypomethylation at the MEA gene. DME can excise 5-methylcytosine in vitro and when expressed in E. coli. Abasic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
779
1
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 645 publications
(820 citation statements)
references
References 44 publications
21
779
1
8
Order By: Relevance
“…The mechanism behind this demethylation has been the subject of many years of research. It was hypothesized that, following a paradigm established in plants [21], deamination and subsequent DNA repair might be involved in DNA demethylation. Deletion of the cytidine deaminase Aid in the mouse provided some support for this model as PGCs in these animals display modest DNA hypermethylation [20].…”
Section: Dna Methylationmentioning
confidence: 99%
“…The mechanism behind this demethylation has been the subject of many years of research. It was hypothesized that, following a paradigm established in plants [21], deamination and subsequent DNA repair might be involved in DNA demethylation. Deletion of the cytidine deaminase Aid in the mouse provided some support for this model as PGCs in these animals display modest DNA hypermethylation [20].…”
Section: Dna Methylationmentioning
confidence: 99%
“…Real-time quantitative PCR has shown that MEA expression in the central cell is inhibited by MEA itself [39]. DME is required for MEA activation [40] and is able to remove methylated cytosine from domains linked to the MEA locus [38 ]. However, the degree of DNA methylation of MEA varies depending on natural Arabidopsis accessions Endosperm in seed growth and development Berger, Grini and Schnittger 667 ) that is reduced in size and whose seed integuments (int) do not elongate, whereas embryo growth is not altered.…”
Section: Coordination Of Maternal and Zygotic Cues During Seed Develomentioning
confidence: 99%
“…[38 ,41]. Moreover, DNA methylation does not play a major role in silencing MEA in vegetative tissues or in pollen [37 ], and loss of DNA methylation on MEA paternal allele does not alter their silenced state in endosperm [36,38 ]. Hence, DNA methylation probably plays a limited regulatory role in MEA imprinting.…”
Section: Coordination Of Maternal and Zygotic Cues During Seed Develomentioning
confidence: 99%
See 1 more Smart Citation
“…Convincing biochemical and genetic evidence indicates that proteins belonging to a plant-specific family of DNA glycosylases directly excise 5mC from DNA and initiate active DNA demethylation through a base excision repair (BER) pathway. [7][8][9] Arabidopsis thaliana REPRESSOR OF SILENCING 1 (ROS1) is a representative member of this 5mC DNA glycosylase family, whose members are uniquely characterized by a discontinuous DNA glycosylase domain, 10 a conserved C-terminal domain that is essential for the catalytic activity, 11,12 and a basic amino-terminal domain that mediates nonspecific binding to DNA but it is not required for catalysis. 13 The understanding of active DNA demethylation mechanisms may have broad implications for epigenetic editing, a new discipline aimed to develop molecular tools to modulate gene expression.…”
Section: Introductionmentioning
confidence: 99%